Data fluency : empowering your organization with effective data communication - Gemignani, Zach; Gemignani, Chris; Galentino, Richard; Schuermann, Patrick (Indianapolis, Indiana : John Wiley & Sons, Inc., 2014)
"A dream come true for those looking to improve their data fluency Analytical data is a powerful tool for growing companies, but what good is it if it hides in the shadows? Bring your data to the forefront with effective visualization and communication approaches, and let Data Fluency: Empowering Your Organization with Effective Communication show you the best tools and strategies for getting the job done right. Learn the best practices of data presentation and the ways that reporting and dashboards can help organizations effectively gauge performance, identify areas for improvement, and communicate results. Topics covered in the book include data reporting and communication, audience and user needs, data presentation tools, layout and styling, and common design failures. Those responsible for analytics, reporting, or BI implementation will find a refreshing take on data and visualization in this resource, as will report, data visualization, and dashboard designers"--Provided by publisher.
Foreword -- Introduction -- Chapter 1. The last mile problem -- Chapter 2. The data fluency framework -- Chapter 3. How organizations struggle with data fluency -- Chapter 4. A consumer's guide to understanding data -- Chapter 5. Data authors: skilled designers of data presentations -- Chapter 6. The data fluent culture -- Chapter 7. The data product ecosystem -- Chapter 8. The journey to data fluency -- Feature. The data fluency -- Appendix A. Designing data products -- Appendix B. Style guide.
Includes bibliographical references and index.
Print version record.
Keywords: Computer graphics; Information visualization; Visual communication; Charts, diagrams, etc -- Design; COMPUTERS -- General; REFERENCE -- Questions & Answers; Organisation; Daten; Visualisierung; Computergrafik; Electronic books; Electronic books